Purity Testing of Cultivar Melon DNA Level (Cucumis melo L.) “Gama Melon Basket” using Surface Plasmon Resonance (SPR) Based on Silver Nanoparticle - Thoyibi T; Muhammad Arifin; Kamsul Abraha (Department of Physics, Sebelas Maret University, 2015)
DNA level of purity has been tested by observing the phenomenon of surface plasmon resonance (SPR) in silver film + silver (Ag) nanoparticles system as DNA sensor using Kretschmann configuration. Surface plasmon resonance (SPR) phenomenon observed in the resonance condition of reflectance spectrum vary with incident angle of laser, beamed toward prism. System is built as a model for DNA purity test instrument that give higher accuracy. DNA purity testing was conducted by placing DNA layer with various ratio on prism in order to get the angle shift value in each sample as a result. Purity level of DNA indicates the DNA quality based on the ratio between the amount of pure DNA compared to the amount of impurity materials (protein). After the deposition of DNA in ratio 1,774, 1,838 and 1,916 SPR angle shifted , and respectively. Characteristic differences of DNA with different purity (ratio) are shown by reflectance value that is getting higher at a smaller ratio, indicates that in the higher DNA ratio the angle shift is getting smaller. SPR angle shift which is occurred before and after DNA deposition shows the sensitivity of SPR as DNA sensor.